"Gaps of deciduousness": cyclical gaps in tropical forests - Gandolfi,Sergius (2009)
A new concept named "gaps of deciduousness" is introduced for the momentary annual bright places that appear under tropical and subtropical deciduous canopy trees when they are leafless, a cyclical kind of gap totally different from treefall gaps, whose importance in the regeneration ecology of these forests until now had not been discussed or evaluated. The aim of this article is to highlight the most significant aspects related to the concept of "gaps of deciduousness" and suggest the importance of developing studies to evaluate its relevance in the discussion of plant species coexistence and biodiversity maintenance in some tropical forests.